Isocyanides: Promising Functionalities in Bioorthogonal Labeling of Biomolecules - Zhu, Yuchen; Liao, Jia-Yu; Qian, Linghui (Frontiers in Chemistry, 2021)
Isocyanides have drawn increasing attention in biological applications due to their attractive properties and unique reactivities, which can undergo various reactions, such as multicomponent reactions, α-addition reactions, [4+1] cycloaddition reactions, and the reaction scope keeps expanding. In addition to acting as reactants for the preparation of structurally interesting and diverse N-heterocycles or peptidomimetics, this type of functionality may be a good choice in the labeling and modulation of biomolecules due to the high biocompatibility and small size to minimize modifications on the parent molecule. It has been demonstrated that isocyanides can participated in biomolecule labeling through three strategies, including the two-component bioorthogonal reaction, multicomponent reaction, and metal chelation. Among which, the isocyanide-tetrazine reaction has been better studied recently, augmenting the potency of isocyanide as a bioorthogonal handle. This review will focus on the recent progress in the isocyanide chemistry for labeling of biomolecules. Meanwhile, methods to introduce isocyano groups into proteins and carbohydrates are also described to facilitate wider applications of this unique functionality.